Invasive Meningococcal Disease Among People Experiencing Homelessness—United States, 2016–2019 . (24th June 2022) - Rudmann, Keegan C; Brown, Nicole E; Rubis, Amy B; Burns, Meagan; Ramsey, April; De Las Nueces, Denise; Martin, Tasha; Barnes, Meghan; Davizon, Emily Spence; Retchless, Adam C; Potts, Caelin; Wang, Xin; et al.
Abstract: Background: Recently, several invasive meningococcal disease (IMD) outbreaks caused by Neisseria meningitidis have occurred among people experiencing homelessness (PEH). However, overall IMD risk among PEH is not well described. We compared incidence and characteristics of IMD among PEH and persons not known to be experiencing homelessness (non-PEH) in the United States. Methods: We analyzed 2016–2019 IMD data from the National Notifiable Diseases Surveillance System and enhanced meningococcal disease surveillance. Incidence was calculated using US census data and point-in-time counts from the US Department of Housing and Urban Development. Results: Of cases from states participating in enhanced surveillance during 2016–2019 (n = 1409), 45 cases (3.2%) occurred among PEH. Annual incidence was higher among PEH (2.12 cases/100 000) than non-PEH (0.11 cases/100 000; relative risk, 19.8; 95% confidence interval [CI], 14.8–26.7). Excluding outbreak-associated cases (PEH n = 18, 40%; non-PEH n = 98, 7.2%), incidence among PEH remained elevated compared to incidence in non-PEH (relative risk, 12.8; 95% CI, 8.8–18.8). Serogroup C was identified in 68.2% of PEH cases compared to 26.4% in non-PEH ( P  < .0001). Conclusions: PEH are at increased risk for IMD. Further assessment is needed to determine the feasibility and potential impact of meningococcal vaccination for PEH in the United States.